Sense of Negative Fraction: An Analysis of the Epistemological Obstacles Encountered by Prospective Teachers - Tatik Retno Murniasih; Vivi Suwanti; Muhammad Noor Kholid; Sri Rahayuningsih; M Qoyum Zuhriawan; Rahmad Firman Yasin (Mathematics Education Journal, 2026)
Fraction sense in the negative domain is important for prospective teachers; however, many epistemological obstacles persist. Research on these obstacles among prospective teachers remains limited. This study aims to identify and describe epistemological obstacles encountered by prospective teachers when employing the sense of negative fractions, as determined by the APOS mental mechanism. The present study used a mix method. The instruments used to obtain quantitative data were a test, while qualitative data were obtained from documentation, interview guidelines, and field notes. Interview subjects were selected based on the type of epistemological obstacles exhibited. The results indicate five epistemological obstacles encountered by prospective teachers when solving problems necessitating the sense of negative fractions. These obstacles encompass the tendency to generalize, false intuitive judgment, and obstacles related to type 1 and type 2 language representation, as well as trial-and-error strategy. The results also reveal obstacles that differ from those documented in the existing literature, namely obstacles in language representation (types 1 and 2) and obstacles in the utilization of trial-and-error strategies. These findings show that prospective teachers encountered five types of epistemological obstacles respected to negative fraction sense problem. While the limited sample size may constrain the generalizability of the findings, a larger cohort could yield divergent results. Future research is recommended to employ gamified digital media to mitigate epistemological obstacles regarding the sense of negative fractions.